2020
DOI: 10.1111/cea.13592
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab in the treatment of adult patients with mastocytosis: A systematic review

Abstract: Background Mastocytosis is associated with mast cell (MC) mediator‐related symptoms for which limited therapies are available. Objective Our aim was to assess the efficacy and safety of omalizumab in the treatment of MC mediator‐related symptoms in adult patients with mastocytosis. Results We identified one multi‐centre retrospective cohort study (39 patients), one retrospective cohort study (13 patients), 4 case series and 10 case reports. No published controlled randomized study was identified. We included 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 40 publications
0
45
0
1
Order By: Relevance
“…Recently, omalizumab has been proposed for mastocytosis patients to treat severe mediator-related symptoms and to prevent anaphylaxis (3,(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101). The drug was indeed found to be effective in the prevention of recurrent episodes of idiopathic anaphylaxis in adults with mastocytosis (91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101), but has only be licensed for use in children over 12 years of age. The results of the XOLMA study has shown that omalizumab was safe and improved mastocytosis symptoms like diarrhea, dizziness, flush and anaphylactic reactions (100).…”
Section: Management Of Anaphylaxismentioning
confidence: 99%
“…Recently, omalizumab has been proposed for mastocytosis patients to treat severe mediator-related symptoms and to prevent anaphylaxis (3,(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101). The drug was indeed found to be effective in the prevention of recurrent episodes of idiopathic anaphylaxis in adults with mastocytosis (91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101), but has only be licensed for use in children over 12 years of age. The results of the XOLMA study has shown that omalizumab was safe and improved mastocytosis symptoms like diarrhea, dizziness, flush and anaphylactic reactions (100).…”
Section: Management Of Anaphylaxismentioning
confidence: 99%
“…Patients with MCAS suffering from recurrent anaphylactic events due to IgE-dependent venom allergy are advised to undergo venom immunotherapy and/or are treated with anti-IgE antibodies (omalizumab) along with precautions to avoid the allergen. [34][35][36] The most dangerous form of MCAS is the mixed variant (primary plus secondary), where both clonal MC (6an MC neoplasm) and an IgE-dependent allergy are found. 36 These patients are at high risk to develop a fatal MCAS event.…”
Section: Categories Of Mastocytosis and Mcas Clinical Manifestationsmentioning
confidence: 99%
“…The clinical efficacy of many of these agents is currently being explored in clinical trials. Finally, for patients with severe allergies and MCAS, and for those who are suffering from severe allergies, MCAS and/or additional aggravating MC conditions (like HAT and/or mastocytosis), application of antibodies removing IgE, such as omalizumab or ligelizumab, or targeting MC tryptase, may represent promising additional approaches 310 - 314 . Finally, a number of inhibitory receptors, such as Siglec-7, Siglec-8, or CD300a, have been identified on human MCs and are currently being validated for their role as therapeutic target sites 315 - 318 .…”
Section: New Treatment Concepts: Targeting Of MC Growth And/or Activamentioning
confidence: 99%